KIR2DL4 (CD158d) genotype influences expression and function in NK cells - Goodridge, Jodie P; Witt, Campbell S; Christiansen, Frank T; Warren, Hilary S (The Journal of immunology (1950), 2003)
The expression and function of the NK cell receptor KIR2DL4 are controversial. Two common alleles of the transmembrane domain of KIR2DL4 exist. The 10A allele with 10 adenines at the end of the transmembrane exon encodes a full length receptor, whereas the 9A allele has only 9 adenines resulting in a frame shift which in turn generates a stop codon early in the first cytoplasmic exon. The possibility that the 10A and 9A alleles might result in differences in expression and function of KIR2DL4 was explored using mAbs to KIR2DL4. Transfection experiments with cDNA from the 10A and 9A alleles revealed significant membrane expression only with the protein encoded by the 10A allele. Analysis of peripheral blood NK cells demonstrated that only in subjects with at least one 10A allele was cell surface expression of KIR2DL4 detectable, and then only on the minor CD56(bright) NK cell subset. The major CD56(dim) NK cell subset did not cell surface express KIR2DL4 but, interestingly, did so after in vitro culture. Functional analysis using cultured NK cells in redirected lysis assays demonstrated that KIR2DL4 is an activating receptor for NK cells with at least one 10A allele. No significant activity was detected for NK cells generated from subjects homozygous for the 9A allele. These data show that genotype influences cell surface expression and function of KIR2DL4 which may account for reported differences in KIR2DL4 expression and function.